2023
DOI: 10.1126/scitranslmed.adg0873
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics identifies prothymosin α restriction of HIV-1 in vivo

Abstract: Host restriction factors play key roles in innate antiviral defense, but it remains poorly understood which of them restricts HIV-1 in vivo. Here, we used single-cell transcriptomic analysis to identify host factors associated with HIV-1 control during acute infection by correlating host gene expression with viral RNA abundance within individual cells. Wide sequencing of cells from one participant with the highest plasma viral load revealed that intracellular viral RNA transcription correlates inversely with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…The gene expression of these infected cells in the CSF showed upregulation in key pathways, highlighting potential cellular mechanisms of HIV persistence and immune evasion. We extend prior studies in blood that have shown that single-cell technologies can identify transcriptionally active HIV-infected cells ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 58%
“…The gene expression of these infected cells in the CSF showed upregulation in key pathways, highlighting potential cellular mechanisms of HIV persistence and immune evasion. We extend prior studies in blood that have shown that single-cell technologies can identify transcriptionally active HIV-infected cells ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 58%
“…These analyses have culminated in novel revelations about the properties of infected cells in PWH on and off suppressive ART, such as preferential infection of Th1-polarized, cytotoxic effector memory cells during early infection 37 ; enrichment of specific transcription factor motifs 38 ; upregulation of pro-survival and immune checkpoint markers 39 ; increased cell proliferation and HIV-1 silencing signatures 40 ; phenotypically distinct T cell subsets targeted in blood and lymph nodes 41 ; and differential expression of host restriction factors. 42 Despite these gains, a knowledge gap remains regarding the cellular environment conducive to latency establishment in vivo , which requires detailed viral transcriptional activity information to distinguish productive versus non-productive infection combined with the host transcriptome. This is supported by findings from in vitro models in which latently infected cells exhibit distinct transcriptomic profiles from virus-expressing cells.…”
Section: Introductionmentioning
confidence: 99%